A comparative kinetic study of SNCR process using ammonia - Javed,M. Tayyeb (2008)
The paper presents comparative kinetic modelling of nitrogen oxides (NOx) removal from flue gases by selective non-catalytic reduction process using ammonia as reducing agent. The computer code SENKIN is used in this study with the three published chemical kinetic mechanisms; Zanoelo, Kilpinen and Skreiberg. Kinetic modeling was performed for an isothermal plug flow reactor at atmospheric pressure so as to compare it with the experimental results. A 500 ppm NOx background in the flue gas is considered and kept constant throughout the investigation. The ammonia performance was modeled in the range of 750 to 1250 ºC using the molar ratios NH3/NOx from 0.25 to 3.0 and residence times up to 1.5 seconds. The modeling using all the mechanisms exhibits and confirms a temperature window of NOx reduction with ammonia. It was observed that 80% of NOx reduction efficiency could be achieved if the flue gas is given 300 msec to react with ammonia, while it is passing through a section within a temperature range of 910 to 1060 ºC (Kilpinen mechanism) or within a temperature range of 925 to 1030 ºC (Zanoelo mechanism) or within a temperature range of 890 to 1090 ºC (Skreiberg mechanism).